Development and Validation of the Head Teachers’ Administrative Style Questionnaire (HASQ): A Tool for Assessing Leadership Practices - Sattar, Abdul; Khurram, Azmat Farooq Ahmad; Asif, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aimed to develop and validate a headteachers' administrative style questionnaire (HASQ) to assess leadership practices. The questionnaire items were adapted from Northouse's 2014 work, encompassing three administrative styles: Autocratic, Democratic, and Laissez-Faire. The HASQ showcased satisfactory internal consistency, as reflected by an overall Cronbach alpha of 0.837, meeting the acceptable reliability threshold. Consequently, the study underscores the HASQ as a valid and reliable tool for assessing the variety and intensity of headteachers' administrative styles. This study strongly recommends that educational stakeholders such as school authorities, researchers, and policymakers use the headteachers' administrative style questionnaire (HASQ) to assess headteachers' administrative styles. The insights gleaned from this tool could prove crucial for enhancing school management strategies and creating effective educational policies. Moreover, the HASQ could catalyze the promotion of more effective administrative styles, potentially contributing to improved educational outcomes.